2020
DOI: 10.1016/j.apgeochem.2020.104712
|View full text |Cite
|
Sign up to set email alerts
|

Transfer processes of potential toxic elements (PTE) between rock-soil systems and soil risk evaluation in the Baoshan area, Yunnan Province, Southwest China

Abstract: Transfer processes of potentially toxic metals (PTMs) between rock-soil systems and soil risk evaluation in the Baoshan area, Yunnan province, Southwest China. Applied Geochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 72 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…This may be why Cluster 3 (soil samples affected by carbon rock) had the second-highest Corg and TC values ( Figure 5 ). Soils in carbonate rock area can have high Corg contents [ 33 ]. Meanwhile, the carbonate rock areas had the highest Mn content and the second-highest TFe 2 O 3 content in the soil ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be why Cluster 3 (soil samples affected by carbon rock) had the second-highest Corg and TC values ( Figure 5 ). Soils in carbonate rock area can have high Corg contents [ 33 ]. Meanwhile, the carbonate rock areas had the highest Mn content and the second-highest TFe 2 O 3 content in the soil ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PTEs that were not evacuated would be significantly enriched in the weathering residue [ 3 ]. Those PTEs would have undergone coprecipitation or adsorption by Fe oxy-hydroxides [ 33 ] and Mn oxy-hydroxides [ 39 ] in residual soil. Meanwhile, higher pH and Corg values can lead to increased adsorption or co-precipitation with oxides/hydroxides of cations of PTEs [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anthropogenic activities are generally regarded as being the primary source of PTEs in the soil in highly developed, urbanized and industrial urban areas [46][47][48][49], mining areas [5,[50][51][52], or agricultural sectors [41,53]. However, a large body of research on this subject supports the importance of the geological background in contributing to higher PTE contents in soil [2,[33][34][35][36][37]54,55].…”
Section: Introductionmentioning
confidence: 99%
“…The PTE levels in soil are frequently elevated due to mineral resources (such as Cu, Pb, Zn, and Hg), as well as carbonate and basalt parent materials [56][57][58][59][60][61][62][63]. This phenomenon can be observed in the soils of the Baoshan area in Yunnan province, southwest China, where mineral resources and carbonate and basalt parent materials are widely distributed [54,55,64]. Previous study has shown the concentrations and the distribution of selected elements (including PTEs) in the soil and river sediments of the Baoshan area, based on the data from the 1: 250,000 scale National Geochemistry Survey of Land Quality project (NGSLQ) and archived river sediment samples collected and analyzed in the Regional Geochemistry-National Reconnaissance (RGNR) program based in this area (6220 km 2 ) [54].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation